Fungi the crucial contributors for nanotechnology: a green chemistry perspective - Moudgil, Aliesha; Chaudhari, Bhushan P. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
Myconanotechnology has gained an exceptional momentum in today’s world. It encompasses a wide range of applications like in agriculture, biomedical, electronics, textiles, cell and molecular biology, nanodevices, and many more. This fast-growing research field has a list of many nanoparticles that have been synthesized from different kinds of fungi. It is an eco-friendly approach that has sidelined the conventional methods of chemical and physical synthesis that require high energy and are toxic and expensive. The fungal-based synthesis gains functionality due to its discrete and diversified advantages that are being explored. Various parameters like temperature, pH, time and concentrations of fungal biomass or extract as well as of the precursor play a vital role in the protocols. These factors have to be optimized for the laboratory as well as industrial scale production. A greater importance to the use of cell-free extracts for nanosynthesis has been given. They contain the enzymes that are reported to be involved in the synthesis mechanisms as reducing agents and capping agents. The role of fungi in nanosynthesis and nanotechnology per se has many patents under its name. Although there are voids in the existing synthesis methods as well as lacunae in the application part that need to be addressed and filled. With an extensive research and work, myconanoparticles can be exploited to the maximum and lead its advancement in new areas.